Isolation, Structural and Functional Characterization of Jackfruit (Artocarpus heterophyllus Lam) Seed Proteins (The Agriculturists, 2020)
With increasing health awareness, the demand for concentrated proteins from plant sources has been rising for direct consumption or to use as an ingredient in food formulation. The characteristic information of any component is prerequisite for its efficient usage in food preparation. This study was undertaken to isolate the protein from jackfruit seeds and characterizing the physicochemical and functional properties of the isolated protein. The protein fraction from jackfruit seed flour was isolated using pH treatments and centrifugation process. The isolated protein was converted into powder form by a vacuum drying and grinding method. Total protein content in the isolate was determined by the Kjeldahl method. The functional properties such as solubility and gelling capacity and secondary structural elements of jackfruit seed protein isolate (JSPI) were studied. The crude JSPI contained 76.89% protein with 58.44% solubility in aquatic solvent. The conformational study by Fourier-transform infrared spectroscopy (FTIR) indicated that the β -sheet is the dominant secondary structure of JSPI that contained 50.28% β -sheet, 21.71% α -helix, 8.86% β -turn, and 19.15% unordered structure. The least gelation concentration of JSPI dissolved in 1.0 M NaCl solution was 12%. The pH of the solvent significantly affected the emulsifying and foaming properties (p